IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH INTERACTIVE READ-ALOUD TECHNIQUE OF THE TENTH GRADE STUDENTS AT MA ALHIDAYAH MUARA TELANG (A CLASSROOM ACTION RESEARCH) - Dahlia Dahlia; Indawan Syahri; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2020)
The research was conducted to improve the tenth-grade students’ reading comprehension on narrative texts through the Interactive read-aloud technique at MA Alhidayah Muara Telang. The problems of this study were (1) most students do not respond to the lesson in the class activity, (2) The students have difficulties to comprehend reading text, (3) The students have a low interest to learn, (4) The students cannot express their response for giving questions about things, because they do not have enough vocabulary. The researcher applied classroom action research which had been conducted into two cycles, where every cycle has three meetings. Each cycle had four steps; they were planning, action, observation, and reflection. Based on the quantitative data, it showed that the students’ reading comprehension on narrative text marked a significant increase from the average score of reading comprehension within the two cycles. In the average score of the test, the first achievements’ score was 74 and the second achievements’ score was 87. The percentage of the first classical achievement was 54 % and the second classical achievements were 93 %. The researcher concluded that the interactive read-aloud technique could improve the students’ reading comprehension of narrative texts significantly.